A Multi-Domain Simulation Study of a Pulsatile-Flow Pump Device for Heart Failure With Preserved Ejection Fraction - Ozturk, Caglar; Rosalia, Luca; Roche, Ellen T. (Frontiers in Physiology, 2022)
Mechanical circulatory support (MCS) devices are currently under development to improve the physiology and hemodynamics of patients with heart failure with preserved ejection fraction (HFpEF). Most of these devices, however, are designed to provide continuous-flow support. While it has been shown that pulsatile support may overcome some of the complications hindering the clinical translation of these devices for other heart failure phenotypes, the effects that it may have on the HFpEF physiology are still unknown. Here, we present a multi-domain simulation study of a pulsatile pump device with left atrial cannulation for HFpEF that aims to alleviate left atrial pressure, commonly elevated in HFpEF. We leverage lumped-parameter modeling to optimize the design of the pulsatile pump, computational fluid dynamic simulations to characterize hydraulic and hemolytic performance, and finite element modeling on the Living Heart Model to evaluate effects on arterial, left atrial and left ventricular hemodynamics and biomechanics. The findings reported in this study suggest that pulsatile-flow support can successfully reduce pressures and associated wall stresses in the left heart, while yielding more physiologic arterial hemodynamics compared to continuous-flow support. This work therefore supports further development and evaluation of pulsatile support MCS devices for HFpEF.